AQUILA HOOP ARENA: AN INTERNATIONAL BASKETBALL COMPETITION FACILITY DESIGN IN SIDOARJO REGENCY WITH A SUSTAINABLE ARCHITECTURE APPROACH - Aira Nabila; Respati Wikantiyoso; Hery Budiyanto; Junianto (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2026)
The Design of Aquila Hoop Arena aims to provide international basketball competition facilities that are adaptive to the tropical climate in Sidoarjo Regency. Sidoarjo was chosen based on considerations of its strategic location near Juanda Airport and adequate infrastructural support. The main challenges in this design are high solar heat intensity and noise pollution from aviation activities. The design method employs a sustainable architectural approach by integrating local fauna. The design results not only implement these two approaches but also a metaphor of a basketball hoop on the building mass and the silhouette of the Garuda bird's wings as a symbol of national strength. Ecological strategies are implemented through a building envelope that adapts the morphology of Pangolin scales to optimize thermal comfort and energy efficiency in the building. Furthermore, the application of the urban forest concept serves as a noise buffer and heat reduction for the arena area. This design is expected to not only become a new sports icon but also a model for public buildings that are responsive to environmental context and locality.